Percutaneous Cryoablation of Metastatic Lesions from Colorectal Cancer: Efficacy and Feasibility with Survival and Cost-Effectiveness Observations. (14th November 2012) - Bang, Hyun J.; Littrup, Peter J.; Currier, Brandt P.; Goodrich, Dylan J.; Choi, Minsig; Heilbrun, Lance K.; Goodman, Allen C.
Abstract : Purpose . To assess feasibility, complications, local tumor recurrences, overall survival (OS) and estimates of cost-effectiveness for multi-site cryoablation (MCA) of oligo-metastatic colorectal cancer (mCRC) in a prospective study. Materials and Methods . 111 CT and/or US-guided percutaneous MCA procedures were performed on 151 tumors in 59 oligo mCRC patients. Mean patient age was 63 years (range 21–92 years), consisting of 29 males and 30 females. Tumor location was grouped according to common metastatic sites. Median OS was determined using the Kaplan-Meier. Estimates of MCA costs per LYG were compared to historical values for systemic therapies. Results . A mean 1.9 MCAs per patient were performed with a median clinical follow-up of 12 months. Major complication and local recurrence rates were 8% (9/111) and 12% (18/151), respectively. Median overall-survival (OS) was 23.6 months with an estimated 3-year survival rate of 30%. Cryoablation remained cost effective with or without the presence of systemic therapies, with an adjunctive cost-effectiveness ratio (ACER) of 39, 661–85, 580 per LYG. Conclusions . Multi-site cryoablation had very low complication and local recurrence rates, and was able to provide local control even for diverse soft tissue locations. Even as an adjunct to systemic therapies, MCA appeared cost-effective, with apparent increased survival.